Use and effectiveness of the Failure Modes and Effects Analysis (FMEA) for identification of potential errors and failures in the process of root canal treatment - Mohsen Yazdanian; Mostafa Alam; Esmail Rafiee; Elahe Tahmasebi; Arash Ghaffarpasand; Kamyar Abbasi; Mohammadkarim Bahadori (University Library System, University of Pittsburgh, 2022)
Background and Aim: Root canal treatment (RCT) has high technical sensitivity, and many human procedural errors can compromise the success of treatment and well-being of patients. The failure modes and effects analysis (FMEA) is a risk assessment and management tool that ensures the safety of patient care by a systematic approach to failures. This study aimed to identify the potential errors and failures in the process of RCT using the FMEA. Materials and Methods: This descriptive study evaluated the failure modes and their effects qualitatively and quantitatively using the FMEA methodology. For this purpose, a FMEA team was first established and the steps of RCT were described in a flowchart. Next, the potential errors and failures in each step were identified, and each failure mode was scored from 1 to 10, based on the severity of impact, likelihood of occurrence, and likelihood of detection. The three scores were multiplied to obtain the risk priority number (RPN). Corrective measures and preventive strategies were suggested for high-risk failure modes (RPN≥250). Results: The FMEA identified 19 steps and 48 potential failures in the process of RCT. The maximum RPN in the process of RCT was assigned to file fracture in the root canal (RPN=324), apical extrusion of irrigating solution (RPN=320), and inappropriate or no rubber dam isolation (RPN=315). Conclusion: The FMEA has high efficacy for detection and prioritization of improvable points in a complex dental procedure in a busy department such as the endodontics department.